ExCo Meeting, Online, 19 November 2020 - (:unkn) unknown (AESOP, 2020)
This is the material for the ExCo Meeting held online on 19 November 2020. AGENDA 01 Welcome 02 Approval of the agenda 03 Approval of the ExCo Meeting Minutes and Resolutions from the July 2020 Meeting 04 The President’s Report 05 The Secretary General’s Report, including - AESOP Membership applications - open and upcoming calls - update on Thematic Group review - update on Transactions 06 Moving AESOP’s registration - update 07 The Conference Officer’s Report, including - update on WPSC 2021 - update on AESOP HoS 2021 - update on AESOP 2021 PhD Workshop - update on AESOP 2022 Congress and PhD Workshop - proposal for additional activities 08 The Treasurer’s Report 09 The Young Academics Network Representative’s Report including - update on AESOP Memories - update on webinars 10 The Quality Recognition Report 11 The GPEAN and UN Habitat Update Report 12 AEKOM Update including - update on website tender 13 AOB The item contains the following files (zipped): 05-a-aesop-membership-applications-full-membership-tu-dublin-profile-03-11-2020.pdf 05-a-aesop-membership-applications-full-membership-tu-dublin-review-by-brendan-williams-03-11-2020.pdf 05-a-aesop-membership-applications-full-membership-tu-dublin-review-by-sina-shahab-03-11-2020.pdf 05-a-aesop-membership-applications-individual-membership-abdullah-faizul-cv-03-11-2020.pdf 05-a-aesop-membership-applications-individual-membership-michele-campagna-cv-18-11-2020.pdf 05-a-aesop-membership-applications-individual-membership-valentina-palermo-cv-03-11-2020.pdf 05-b-open-and-upcoming-call-draft-call-for-aesop-president-2022-2024-03-11-2020.docx 05-c-update-on-thematic-group-overview-letter-to-exco-from-planning-conflict-coordinator-03-11-2020.pdf 05-c-update-on-thematic-group-overview-tg-planning-and-complexity-funding-application-17-11-2020.docx 05-secretary-general-s-report-18-11-2020.docx 07-b-update-on-aesop-hos-2021-17-11-2020.pdf 07-conference-officer-slides-19-11-2020.pptx 07-c-update-on-aesop-2021-phd-workshop-contract-03-11-2020.doc 07-c-update-on-aesop-2021-phd-workshop-update-17-11-2020.pdf 07-iii-update-on-aesop-congress-2022-video-links-19-11-2020.docx 07-iv-email-to-aesop-tg-s-to-host-2021-events-18-11-2020.docx 09-ya-activity-report-12-11-2020.docx 11-gpean-update-16-11-2020.pdf 12-aekom-bid-for-website-tender-limpide-16-11-2020.pdf 12-aekom-update-slides-19-11-2020.pptx 12-aekom-update-slides-19-11-2020 (1).pptx aesop-assets-2020-15-11-2020.pdf aesop-budget-2020-19-11-2020.pdf draft-corep-minutes-july-2020-03-11-2020.docx draft-corep-resolutions-july-2020-03-11-2020.docx draft-exco-minutes-july-2020-03-11-2020.docx draft-exco-resolutions-july-2020-03-11-2020.docx exco-agenda-20-10-2020.pdf how-to-join-the-meeting-20-10-2020.pdf matters-arising-corep-july-2020-03-11-2020.docx matters-arising-exco-july-2020-03-11-2020.docx meeting-interface-features-overview-20-10-2020.pdf Read me.rtf
Keywords: ExCo online 2020; material; minutes; agenda